2021
DOI: 10.31729/jnma.6605
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco and its Relationship with Oral Health

Abstract: Tobacco and its various forms cause major oral health problems. Tobacco either in smoked or smokeless forms is prevalent in Nepal and counts as a risk factor for the causation of various red and white lesions, premalignant lesions, oral cancers, gingival and periodontal diseases. Tobacco in conjunction with other risk factors adds a potential threat to oral diseases and its timely control is a cure to those threats. This article focuses on tobacco and its forms affecting oral health and also focuses on its pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Young non-smokers, IQOS ® users, or cigarette smokers should be properly informed and educated about the benefits of non-smoking by general health or dental practitioners because they can be easily misled by well-thought-out marketing of the tobacco industry. Reduced risks of periodontal disease, enhanced healing and recovery of the periodontium, and improved esthetics of the teeth with regard to discoloration of teeth, gums, and bad breath are all key arguments to encourage non-smokers to remain non-smokers and smokers to abandon their bad habit [4,30].…”
Section: Discussionmentioning
confidence: 99%
“…Young non-smokers, IQOS ® users, or cigarette smokers should be properly informed and educated about the benefits of non-smoking by general health or dental practitioners because they can be easily misled by well-thought-out marketing of the tobacco industry. Reduced risks of periodontal disease, enhanced healing and recovery of the periodontium, and improved esthetics of the teeth with regard to discoloration of teeth, gums, and bad breath are all key arguments to encourage non-smokers to remain non-smokers and smokers to abandon their bad habit [4,30].…”
Section: Discussionmentioning
confidence: 99%
“…More than half of the study population exhibited the adverse habit of chewing tobacco and gutkha, indicating that people were not aware of the harmful effects of tobacco. Tobacco contains a harmful chemical called nicotine, which has adverse effects on oral health [ 10 , 11 ]. The adverse effects include the development of periodontitis, halitosis, development of oral mucosal lesions, oral cancer, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, blueberry extract has been shown to inhibit The Janus-Kinase signal transducer and the transcription activation pathway (JAK/STAT-3) signaling by modulating the downstream sites affecting cell proliferation and apoptosis in a hamster model of oral oncogenesis [ 120 ]. Therefore, due to the action of this phytochemical, it is possible to inhibit oral carcinogenesis by alcohol, which is an important inducing factor of this type of cancer that can contribute to the large number of people who regularly consume this substance [ 173 , 174 ]. Other studies have shown the chemopreventive capacity of grape wine in cells of the oral mucosa.…”
Section: Berries and Cancermentioning
confidence: 99%